ANALISIS PENGARUH PENDIDIKAN, PERTUMBUHAN PENDUDUK DAN INVESTASI TERHADAP KEMISKINAN DI KALIMANTAN SELATAN - LELI SAFITRI; MUHAMMAD EFFENDI (PPJP Universitas Lambung Mangkurat, 2019)
Poverty is a complex problem in a development and related to many aspects. The problem of poverty has a close relation with low level of income received by the labors which caused of education quality that still in low level, the population growth which relatively high may caused more unemployment, a different growth of investment in every region that may difficult to create more job field for poor people, if economic growth in a region only dominated by a certain production activities and using more labors with high education background from other regions, and it caused poor people should to live in poverty circle.This research is a quantitative research and using the analysis of panel data.Data from period 2013-2017 and which including all of the regencies/cities in South Kalimantan that consists of 13 regencies/cities. The purpose of this research is to analyze how big the effect of education, population growth and investment towards poverty in South Kalimantan.The result shows that education has a negative effect and not significant, population growth has a negative effect and significant and investment has a positive effect and not significant towards poverty in South Kalimantan. Keywords : Poverty, Education, Population Growth, Investment